Recognition of oral potentially malignant disorders and transformation to oral cancer. Issue 11 (November 2020) - Vail, Marianne; Robinson, Sean; Condon, Heather
Abstract : ABSTRACT: Oral potentially malignant disorders refer to oral mucosal disorders with increased risk for malignant transformation, primarily to oral squamous cell carcinoma (SCC). Leukoplakia and erythroplakia are the most common of these disorders, but others have been identified. Transformation rates to oral cancer vary based on multiple factors. Healthcare providers should be aware of risk factors and clinical manifestations of these disorders and should intervene early to monitor and/or treat them to reduce the potential for malignant transformation.